Le Néolithique ancien en Italie du sud : evolution des industries lithiques entre Vlle et Vle millénaire - Collina, Carmine, (Archaeopress archaeology., 2015)
The principal aim of this study is to put forward a technological and typological analysis of the industries of the Early Neolithic concerned in the process of neolithisation in several regions of Southern Italy.